2021
DOI: 10.14742/ajet.6073
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting student-teacher satisfaction with a multi-college online collaborative course

Abstract: This study examined the factors that may promote student-teachers’ satisfaction with online collaborative learning (OCL). Eighty-four student teachers at the graduate level at three teacher-education colleges in Israel simultaneously completed questionnaires that examined their information and communication technology (ICT) skills, collaboration experience and personality traits. The findings reveal that ICT level, positive experiences with collaborative learning and openness contributed significantly to satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
2
10
1
Order By: Relevance
“…Furthermore, the sample students preferred collaborative activities throughout the online course. This finding agrees with the literature where adequate peer-to-peer interaction, guided by the instructor, can establish an online community to facilitate co-construction of knowledge and enhance satisfaction (Abuhassna et al, 2020;Kuzmanović et al, 2019;Lee et al, 2019, Ng & Baharom, 2018Shonfeld, 2021). Activities that strengthen this kind of interaction are student-moderated discussions, where participants engage in a dialogue on topics that are open to interpretations (P. .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the sample students preferred collaborative activities throughout the online course. This finding agrees with the literature where adequate peer-to-peer interaction, guided by the instructor, can establish an online community to facilitate co-construction of knowledge and enhance satisfaction (Abuhassna et al, 2020;Kuzmanović et al, 2019;Lee et al, 2019, Ng & Baharom, 2018Shonfeld, 2021). Activities that strengthen this kind of interaction are student-moderated discussions, where participants engage in a dialogue on topics that are open to interpretations (P. .…”
Section: Discussionsupporting
confidence: 88%
“…Mutual collaboration for the co-construction of knowledge can increase students' satisfaction (Lee et al, 2019;Shonfeld, 2021); a sense of connection derives from belonging to a group. Regarding assessment, though, students might prefer individual assignments (Heilporn & Desrochers, 2020).…”
Section: Students' Perceptions and Preferences In Distance Educationmentioning
confidence: 99%
“…refs. [4], [6], [7], [22], [23]). While we recognize that correlation does not necessarily mean causality, we are encouraged by the parallel results of all three experiments and present the modified conceptual model shown in Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have tried to analyze the key elements of student satisfaction at higher education in different ways. For example, Shonfeld [6] recognized the following three components: instructors, quality, and teaching methods. On the other hand, Alnawas [7] identified the following factors: organization and management, quality of teaching, personal development, assessment and feedback, learning resources and academic support.…”
Section: Modeling Student Satisfactionmentioning
confidence: 99%
“…Among the many studies on the factors that affect online collaborative learning, it is found that the information technology level of teachers and learners is a prerequisite for collaborative learning based on computer information technology [22]. Therefore, how to reduce the learning cost of information technology for teachers and learners and overcome the barriers to use should be the direction of efforts to improve the effect of collaborative learning, and the collaboration software represented by Git is also gradually recognized by the market and users because of its ease of use and powerful functions.…”
Section: Collaborative Learningmentioning
confidence: 99%